ANALISIS FAKTOR YANG MEMPENGARUHI PENERIMAAN PELANGGAN PLN ULP BANYUWANGI KOTA TERHADAP APLIKASI NEW PLN MOBILE - Dwi Mulyono; Gancar C. Premananto (Politeknik Negeri Lhokseumawe, 2022)
Abstract: The purposes of this research was to analyze the effect of Technology Acceptance Management (TAM) variables to explain the factors that affect acceptance to using New PLN Mobile application on costumer of PLN ULP Banyuwangi Kota. In this research analyzed the effect of information quality, relative advantage and perceived enjoyment on perceived ease of use and perceived usefulness, the effect of perceived ease of use on perceived usefulness and attitude toward using, the effect of perceived usefulness on attitude toward using and intention to use as well as the effect attitude toward using on intention to use. This research was a quantitative research done by survey method. Data collected by distributing questionaire to 226 samples whom are the costumer of PLN ULP Banyuwangi Kota. The samples determine by purposive sampling method. Data analysis done by Structural Equation Modelling use SmartPLS software. The research result shown that information quality and perceived enjoyment have no significat effect on perceived ease of use and perceived usefulness; relative advantage have significant positive effect on perceived ease of use and perceived usefulness. Furthermore also found that perceived ease of use have significant positive effect on perceived usefulness and attitude toward using; perceived usefulness have significant positive effect on attitude toward using and intention to use; as well as attitude toward using have significant positive effect on intention to useKeyword: information quality, relative advantage, perceived enjoyment, perceived ease of use, perceived usefulness, attitude toward using, and intention to use